Physical Functioning, Perceived Disability, and Depressive Symptoms in Adults with Arthritis. (5th September 2013) - Becofsky, Katie; Baruth, Meghan; Wilcox, Sara
Abstract : This study investigated how physical functioning and perceived disability are related to depressive symptoms in adults with arthritis (n = 401 ). Participants self-reported depressive symptoms and disability. Objective measures of physical functioning included the 30-second chair stand test, 6-minute walk test, gait speed, balance, grip strength, and the seated reach test. Separate quantile regression models tested associations between each functional measure and depressive symptoms, controlling for age, gender, race, BMI, self-reported health status, and arthritis medication use. The association between perceived disability and depressive symptoms was also tested. Participants averaged 56.3 ± 10.7 years; 85.8% were women; 64.3% were white. Lower distance in the 6-minute walk test, fewer chair stands, slower gait speed, and greater perceived disability were associated with greater depressive symptoms in unadjusted models (Ps < 0. 05 ). Fewer chair stands and greater perceived disability were associated with more depressive symptoms in adjusted models (Ps < 0. 05 ). Balance, grip strength, and seated reach were not related to depressive symptoms. The perception of being disabled was more strongly associated with depressive symptoms than reduced physical functioning. To reduce the risk of depression in arthritic populations, it may be critical to not only address physical symptoms but also to emphasize coping skills and arthritis self-efficacy.